Intercultural Competence: Another Challenge - Norma Barletta Manjarrés (Universidad Nacional de Colombia, 2009)
This paper intends to draw the attention of language teachers and educational authorities to the area of culture teaching in foreign language education at a time when the recently issued Basic Standards of Competencies in Foreign Language have conferred modest attention to this aspect of language education. The paper first describes the notion of Intercultural communicative competence. It then discusses the tensions between this new understanding of the teaching of culture and the prevailing teaching practices, approaches, beliefs and discourses associated with the learning and teaching of culture. Third, it reports on the results of a study which critically analyzed the academic discourses of in-service teachers in Colombia regarding the cultural component of foreign language programs; finally, it proposes ways to start taking new directions.